Sistematik Review Integrasi Hukum, Ekonomi, dan Biologi dalam Pengelolaan Sumber Daya Alam: Evaluasi Kebijakan, Dampak Ekonomi, dan Konservasi Ekosistem - La Husen, Debi; Ibrahim, Arisman Suar Bhakti; Ridwan (Jurnal Sains dan Pendidikan Biologi, 2024)
Sustainable natural resource management requires effective integration of law, economics, and biology. This study aims to conduct a systematic review of the literature exploring the interactions between these three disciplines in the context of natural resource management. The methodology includes literature collection from academic databases, quality assessment of studies, and thematic analysis to identify key patterns and themes. The review findings indicate that stringent legal policies, such as species protection laws and conservation areas, are effective in mitigating the negative impacts of economic activities on the environment. Economic approaches, such as cap-and-trade systems and incentives for sustainable practices, have also proven effective in reducing pollution emissions and enhancing resource efficiency. However, this integration faces significant challenges, including differing objectives between law, economics, and biology, as well as a lack of current biological data. To address these challenges, a collaborative approach involving scientists, policymakers, and practitioners is needed to develop policies that holistically incorporate legal, economic, and biological considerations. Recommendations from this review include enhancing biological data collection, developing economic incentives that support sustainability, and ensuring consistent law enforcement to achieve more sustainable natural resource management.